2011
DOI: 10.1016/j.bbamem.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of daptomycin on membranes

Abstract: Daptomycin is a lipopeptide antibiotic that kills Gram-positive bacteria by membrane depolarization. While it has long been assumed that the mode of action of daptomycin involves the formation of membrane-associated oligomers, this has so far not been experimentally demonstrated. We here use FRET between native daptomycin and an NBD-labeled daptomycin derivative to show that such oligomerization indeed occurs. The oligomers are observed in the presence of calcium ions on membrane vesicles isolated from Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 24 publications
6
158
1
2
Order By: Relevance
“…Fluorescence experiments using micromolar concentrations of two derivatives of daptomycin labelled with Alexa Fluor 350 and 7-nitro-2,1,3-benzoxadiazol (NBD-Dap; Figure 3) detected no FRET between both, with or without Ca 2+ present, 45 suggesting that aggregation does not occur at concentrations near the MIC. It cannot be ruled out, however, that the covalently attached fluorescent labels may have affected the extent of aggregation.…”
Section: Calcium-induced Aggregation and Its Role In Daptomycin Delivmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence experiments using micromolar concentrations of two derivatives of daptomycin labelled with Alexa Fluor 350 and 7-nitro-2,1,3-benzoxadiazol (NBD-Dap; Figure 3) detected no FRET between both, with or without Ca 2+ present, 45 suggesting that aggregation does not occur at concentrations near the MIC. It cannot be ruled out, however, that the covalently attached fluorescent labels may have affected the extent of aggregation.…”
Section: Calcium-induced Aggregation and Its Role In Daptomycin Delivmentioning
confidence: 99%
“…Accordingly, the proposal by Silverman et al 73 that daptomycin also forms oligomeric membrane pores or channels was quite readily accepted, although at the time no experimental evidence of oligomer formation had been obtained. More recently, Muraih et al 45 demonstrated oligomer formation on liposomes and on bacterial membrane vesicles by FRET, using the Kyn (13) residue of unlabelled daptomycin as the donor and an extrinsic NBD moiety attached to Orn (6) as the acceptor (NBDdaptomycin, Figure 3). When NBD-daptomycin was used alone, oligomer formation was also evident by self-quenching of the dye.…”
Section: Daptomycin Oligomer Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Daptomycin, however, exhibits a different mechanism of action, as Ca 2ϩ helps daptomycin to interact with and aggregate in the membrane (2,15,19,24), leading to membrane depolarization and eventual bacterial cell death (28). Nevertheless, the presence of Ca 2ϩ had less of an effect on the activity and secondary structure/membrane interaction of MX-2401 than on those of daptomycin, consistent with its different mechanism of action, inhibiting the biosynthesis of the cell wall and teichoic acid precursors (25).…”
mentioning
confidence: 99%
“…The addition of one or more equivalents of Ca 2ϩ completely inverted the positive ellipticity at 230 nm in the absence of calcium. This effect has been interpreted as being due to a Ca 2ϩ -dependent change in structure (15,19) or daptomycin-mediated fusion of POPC-POPG liposomes in the presence of calcium (16) without a structural change (12).…”
mentioning
confidence: 99%